STAGES AND FEATURES OF EDUCATIONAL TOURISM DEVELOPMENT (Academicia Globe: Inderscience Research, 2024)
The article presents definitions of educational tourism. It also discusses the role of educational tourism as a mechanism for intercultural communication. The stages of development of educational tourism from its first manifestations to the present day are covered. An analysis of international educational visits of students and the income from them, as well as the indicators of countries receiving the highest income from educational tourism, is presented using the example of Canada.